Information Computing and Applications Third International Conference, ICICA 2012, Chengde, China, September 14-16, 2012. Proceedings - Liu, Baoxiang; Ma, Maode; Chang, Jincai; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the Third International Conference on Information Computing and Applications, ICICA 2012, held in Chengde, China, in September 2012. The 100 revised full papers were carefully reviewed and selected from 1089 submissions. The papers are organized in topical sections on internet computing and applications, multimedia networking and computing, intelligent computing and applications, computational statistics and applications, cloud and evolutionary computing, computer engineering and applications, knowledge management and applications, communication technology and applications.
internet computing and applications -- multimedia networking and computing -- intelligent computing and applications -- computational statistics and applications -- cloud and evolutionary computing -- computer engineering and applications -- knowledge management and applications -- communication technology and applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Management information systems; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering; Information Systems Applications (incl. Internet).; Probability and Statistics in Computer Science; Business Information Systems